Penetration of Islamic Puritan Learning in Vellages: Study on Cadreation of Members Of Al-Qur'an Interpretation Forum in Nganjuk Regency - Saputri, Nur Aini Elvin (Didaktika Religia, 2018)
This study discusses the social penetration of the Al-Qur'an Puritanical Interpretation Council (MTA) both in development and cadre regeneration of its members in Nganjuk Regency. The movement of social puritanical Qur’an Interpretation Forum carried out by the MTA are very interesting to study. Although in the form of a foundation with charismatic leadership, MTA preaches puritans such as social organizations, because it has an active organizational structure. Most MTA members from various backgrounds include farmers, laborers, and government officials. There are various factors that tremble behind them, one of which is being laymen, material benefit and a democratic movement. The pattern of cadre MTA members in Nganjuk regency has 4 stages, namely introduction, coaching, stabilization, and control.